Jarak Kehamilan terhadap Kejadian Kala 1 Fase Aktif Memanjang - Maulana Idham Lutfi; Silitonga, Reisyah Dinda Syahfira; Zulfadli, Zulfadli (CV. Jasa Sukses Abadi, 2024)
Prolonged labor or what is called dystocia is a condition where the labor process experiences difficulties with slow progress. Signs indicating dystocia include a low-lying fetal presentation that fails to enter the pelvis on Leopold's examination, slow cervical dilatation, and a loose presenting part into the cervix. There are several factors that can cause dystocia including the strength of uterine contractions (power), condition of the birth canal (passage), position and size of the fetus (passenger), number of previous pregnancies (parity), premature rupture of membranes, mother's age, distance between pregnancies, social conditions economy, and the level of response to stress. A gap between pregnancies that is too long (>10 years) can increase the risk of dystocia during delivery. This study is a case report. Data was obtained from a 35 year old woman who complained of being at term pregnant with heartburn since 1 day before entering the hospital (SMRS). The patient admitted that abdominal pain had spread to the waist since 1 day before entering the hospital (SMRS). The patient then had an examination with the midwife and it was said to be opening 2, then the patient was sent home. On June 4 2024 at 11 am the patient underwent an examination with a gynecologist and was given misoprostol 50 mcg and then the patient complained of increasingly frequent heartburn. At 15.30 the patient was checked again by the midwife and found that it was 4 cm dilated, it was observed until 22.30 and it remained 4 cm dilated, then the patient was referred to RSAM. The patient admitted that she was pregnant at term and still felt the baby's movements. Pregnancy spacing is the most important factor in these patients. This pregnancy is the patient's second pregnancy, the first pregnancy was in 2012 which was born at term, vaginally, male with a birth weight of 2800 grams. Several previous studies have shown that there is a relationship between pregnancy spacing and the incidence of prolonged labor, but there is no theory that is considered absolutely correct to date. Therefore, intervention is needed for early prevention and early management of prolonged labor, especially regarding prevention of too long a pregnancy distance.